P71 Giant ovarian cyst with progression potential- clinico-pathological aspects. (6th June 2017) - Stepan, Mioara Desdemona; Niculescu, Carmen Elena; Puiu, Ileana; Moroşanu, Aritina Elvira; Dop, Dalia; Stoica, Alin; Stepan, Alex
Abstract : Background and aims: Giant ovarian cysts are rare clinical entities in teenage, mainly benign and sometimes asymptomatic, leading to a delay in diagnosis and with potentially severe complications. In this study we present a giant ovarian cyst with tumour progression potential. Methods: In order to establish the diagnosis we used clinical, paraclinical, imaging and histopathological investigations. To investigate the progression potential of the lesion we have analysed the immunohistochemical positivity index for anti-human Ki67 and P53 monoclonal antibodies, and reported the data as percentage of labelled cells. Results: We present the case of a 15-year-old teenager, admitted to the Paediatric Clinic of the Emergency County Hospital Craiova for diffuse abdominal pain, fatigue, loss of appetite, abdominal enlargement, with onset about 2 years, for which she did not performed paraclinical or imaging investigations. The physical examination indicated average influenced overall condition, distended abdomen with decline dullness, diffuse spontaneous and induced upon palpation pain. The imaging examinations performed in the clinic (abdominal ultrasound, abdominal computed tomography) indicated the suspicion of a left cystic giant ovarian structure of 24/10/22 cm, for which was practiced the laparoscopic cure in the Paediatric Surgery Clinic. The histopathological analysis revealed the diagnosis of ovarian serous cystadenoma with bordeline areas. The immunohistochemical reactions indicated a positivity index of 8% for Ki67 and of 10% for p53, which designated the investigated cyst asa benign lesion with tumour progression potential. Conclusion: The ovarian pathology should be included in the differential diagnosis of abdominal distension for its asymptomatic evolution with risk for severe complications, including impairment of fertility and tumour progression.